Pediatric ethmoid sinus desmoplastic fibroma: Case report and review of pediatric bony sinus tumors. Issue 3 (September 2015) - Kadakia, Sameep; Patel, Neha; Iacob, Codrin; Khorsandi, Azita; Persky, Mark; Bernstein, Joseph
Abstract: While intraosseous tumors of the pediatric sinonasal tract are rare and tend to be slow growing, they can be locally aggressive and have a tendency to recur. Due to the possibility of devastating outcomes secondary to mass effect, it is important for physicians to promptly diagnose and properly manage these tumors. We report an extremely rare case of a desmoplastic fibroma of the ethmoid sinus in a pediatric patient and review its clinical findings, methods of diagnosis, and treatment.